ESPIRITUALIDADE NO MUNDO CORPORATIVO: APROXIMAÇÕES ENTRE PRÁTICA RELIGIOSA E VIDA PROFISSIONAL - Kivitz, Ed René (2007)
Corporate World Spirituality. Approaching Religious Práxis and Professional Life, involving Religion Science, specifically the area society religious Praxis. It was investigated according to critic historical method, using a bibliographic and documental research as data retrieval method. This study aimed evaluating two different hypothesis: corporate world spirituality as a response to contemporary society spiritual needs, replacing institutionalized religious expressions, and corporate world spirituality as a concept that is complementary to religious praxis, aiming human promotion both on market and society. The spirituality concept in Paul Tillich and praxis in Cassiano Floristán were used as the theoretical references for this study. This dissertation was structured in three chapters: the first involving definitions and term listing for spirituality semantic field determination: spirituality and religion, religious and laic, sacred and profane. The second recording movement origins, its blossom, main characters, scientific, ideological, religious, economic and philosophical context, and most importantly, listing the different concepts the word spirituality may assume in corporate world. This chapter clarifies the social and historic factors allowing spirituality to enter the work place and its inclusion on corporate world. Finally, the third chapter evaluates three different possibilities for using the corporate world spirituality concept: spirituality at service of religion (proselytism), of capital (performance) or of the human being (praxis). Thus, this dissertation aims allowing the reader expand knowledge basis on this subject.(AU)